MENGAPA MATA PELAJARAN FISlKA SELALU PALING JELEK? - Krips, Frans (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 1993)
The thought presented emerged from personal experience and reflection, and informal interviews. Eleven reasons proposed by those people interested in physics, includes its level of difficulty; its structure and formal operation; gap between physics andphysics education; gradeon physicsasthe indicatorof students' quality; non selective equpments used in lower secondary level; mismatch between students' conseptions and their scientific concepts emerging from varying terms and language usage; different view of physics teachers' love in physics and physicists' love in history of physics;Â imbalance omount of concepts to be studied and effective hours in school; inappropriate topics sequence; and physics education and its presentation which favour male students. Those reasons are tentative and requiring further clarification by educationists with physics backgrounds.ABSTRAKStudi untuk menjawab pertanyaan di atas dan